The Effect of Targeted Ball Throwing Training on Smash Accuracy of Volleyball - Muhammad Salahuddin; Hariadi Said; Bahtiar Juadi (IKIP Budi Utomo Malang, 2022)
Based on the background of the problems in the TBL club, the aim of this research is to practice target ball throwing against the accuracy of the volleyball smash at the TBL Junior Volleyball Club, Taliabu Regency. The research objective is to determine the effect of target ball throwing training on smash accuracy of volleyball at the TBL Junior Club, Taliabu Regency. The population were 10 people. The method of this research used one group pretest-posttest. The research design used experiment, it has a pre-test post-test. Based on the results of the t-test of the pre-test data and the post test on smash accuracy of volleyball at the TBL junior club, Taliabu Regency, it can be obtained a significance value of 0.000 < 0.05, which means that there is an influence in the pre-test to the post-test on smash accuracy of volleyball at the TBL juniors club in Taliabu Regency with a significant target ball throwing practice, judging from the average score for the final test of 16.90 minus the initial test of 14.00. With these results, it shows an increase in the average value of 2.90.